2010
DOI: 10.1002/jsfa.3861
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic hydrolysis of Alaska pollack (Theragra chalcogramma) skin and antioxidant activity of the resulting hydrolysate

Abstract: This study demonstrated that the hydrolysate of Alaska pollack skin was mainly composed of oligopeptides with two to eight amino acid residues and possessed antioxidant activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(49 citation statements)
references
References 24 publications
3
45
0
1
Order By: Relevance
“…At higher concentrations, P1-1U had the highest DPPH radical scavenging activity, whilst P2-2U showed the lowest activity. DPPH radical scavenging activity was previously reported in protein hydrolysates prepared from the skin of seabass (Senphan and Benjakul 2014), catfish (Alemán et al 2011), Alaska pollack (Jia et al 2010) and bigeye snapper (Phanturat et al 2010). Increasing quantities of active peptides react with free radicals to convert them to stable products (Batista et al 2010).…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 91%
“…At higher concentrations, P1-1U had the highest DPPH radical scavenging activity, whilst P2-2U showed the lowest activity. DPPH radical scavenging activity was previously reported in protein hydrolysates prepared from the skin of seabass (Senphan and Benjakul 2014), catfish (Alemán et al 2011), Alaska pollack (Jia et al 2010) and bigeye snapper (Phanturat et al 2010). Increasing quantities of active peptides react with free radicals to convert them to stable products (Batista et al 2010).…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 91%
“…It can be seen that the antioxidant activity significantly increased with increasing the peptides concentrations in the collagen hydrolysate (Table 3) and reached a maximum value of 84.7 %±0.24 at a concentration of 50.0 mg/ml. Jia et al (2010) applied various microbial proteases to produce collagen peptides with antioxidant activity, and the highest antioxidant activity (44.09 %±1.37) was obtained with protease produced by Bacillus licheniformis.…”
Section: Antioxidant Activity Of Collagen Hydrolysatesmentioning
confidence: 99%
“…Recently, a number of studies have demonstrated that peptides derived from different marine collagen and gelatin hydrolysates act as potential antioxidants and have been isolated from marine organisms such as jumbo squid Rajapakse et al 2005 ), oyster (Qian et al 2008 ), blue mussel , hoki (Je et al 2005 ;Kim and Mendis 2006 ;Mendis et al 2005 ), tuna (Je et al 2007 ), cod (Šližytė et al 2009 ), mackerel (Wu et al 2003 ), Alaska pollock (Je et al 2005 ;Jia et al 2010 ), yellowstripe trevally (Klompong et al 2009 ), mackerel muscle protein (Wu et al 2003 ), conger eel (Ranathunga et al 2006 ), squid skin gelatin Rajapakse et al 2005 ), fi sh skin gelatin , tuna backbone (Je et al 2007 ), tuna cooking juice (Hsu et al 2009 ), cobia ( Rachycentron canadum ) (Yang et al 2008b ), microalgae (Sheih et al 2009 ), and sole ), as well as from several squid species, such as giant squid ( Dosidicus gigas ) , jumbo fl ying squid ( Dosidicus eschrichitii Steenstrup ) (Lin and Li 2006 ), or squid ( Todarodes pacifi cus ) ).…”
Section: Antioxidantmentioning
confidence: 99%